Pemberdayaan Masyarakat dan Peningkatan Nilai Tambah Rumput Melalui Pelatihan Produksi dan Pemasaran Muffin - Kasmiati, Kasmiati; Irda Handayani; Metusalach; Dian Anggareace Sigit Parawansa (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Seaweed is an excellent fishery commodity with low added value because it is mostly sold in dried form, not yet optimally utilized in product diversification programs. This community service activity aims to improve the knowledge and skills of Baji Ampe Partner in utilizing seaweed as a raw material for making muffin to gain its added value. The implementation method of the activity is counseling, practice, and mentoring. Pre-test and post-test were conducted to assess the baseline knowledge of partner and its improvement before and after participating in the activity. The delivery of material on nutrition and utilization of seaweed as well as diversification and the application of hygiene in processing by competent and experienced speakers through lecture and interactive discussions. The practice of making seaweed muffin was carried out in stages with the active participation of Baji Ampe Partner guided by experienced instructors. Mentoring to evaluate the ability of participants to produce and sale products independently while assessing the improvement of participants' skills. The results of the activity showed that the initial knowledge of partner was relatively low, an average of 26%, increasing sharply by 70% to 96% after participating in the training. Likewise, the skill of making seaweed muffin became 100% at the end of the activity from an initial skill of 0%. The muffin-making innovation resulted in an eight-fold increase in added value per kilogram of seaweed, representing a 172,800 rupiah increase. The conclusion of the activity was that the training and mentoring successfully increased the level of empowerment in diversifying products to increase the added value of seaweed. Similar activities can be replicated in other coastal communities as an effort to utilize local resources to improve group welfare.